Data integration dashboard for assessing and planning sustainable intensification agricultural interventions: a case study in Senegal - Santiago, Gustavo N.; Carcedo, Ana J. P.; Brown, Molly E.; Nejadhashemi, A. Pouyan; Prasad, P. V. Vara; Ciampitti, Ignacio A. (Frontiers in Sustainable Food Systems, 2023)
Introduction The lack of a holistic view of agriculture’s social and economic aspects emerges as a limiting factor in policy implementations of sustainable intensification. The aim of this study was to (i) synthesize data from the five domains of sustainable agriculture intensification framework focusing on Senegal as a case study, (ii) harmonize and scale data used to minimize spatial–temporal differences, and (iii) build a digital tool aiming researchers and policymakers to facilitate the data visualization and connection. Methods We propose and prototype an interactive digital decision-support tool as a potential solution to integrate environmental, social, economic, human and production domains in agriculture projects. To demonstrate the use of the tool, a case study using data from Senegal was developed to show the benefits of open science and connectivity among domains. Results and discussion The digital tool presented here allows users to explore an open repository from Senegal serving as a foundational approach to integrate diverse agricultural domains when developing sustainable intensification projects.